Construct validity of the anglicised FACE-Q skin cancer module. Issue 5 (May 2022) - Dobbs, T.D.; Harrison, C.J.; Ottenhof, M.J.; Gibson, J.A.G.; Matin, R.N.; Rodrigues, J.N.; Hutchings, H.A.; Whitaker, I.S.
Summary: Objectives: The FACE-Q Skin Cancer module is a patient-reported outcome measure (PROM) for facial skin cancer. It has been anglicised for the UK population and undergone psychometric testing using classical test theory. In this study, further evaluation of construct validity using Rasch measurement theory and hypothesis testing was performed. Methods: Patients were prospectively recruited to the Patient-Reported Outcome Measures In Skin Cancer Reconstruction (PROMISCR) study and asked to complete the anglicised FACE-Q Skin Cancer module. The scalability and unidimensionality of the data were assessed with a Mokken analysis prior to Rasch analysis. Response thresholds, targeting, fit statistics, local dependency, and internal consistency were examined for all items and subscales. Four a priori hypotheses were tested to evaluate the convergent and divergent validity. We additionally hypothesised that the median 'cancer worry' score would be lower in post-operative than pre-operative patients. Results: 239 patients self-completed the questionnaire between August 2017 and May 2019. Of the ten subscales assessed, five showed relative fit to the Rasch model. Unidimensionality was present for all five subscales, with most demonstrating ordered item thresholds and appropriate fit statistics. Two items in the 'cancer worry' subscale had either disordered or very close response thresholds. Subscales of the FACE-Q Skin Cancer module demonstrated convergent and divergent validity with relevant Skin Cancer Index comparators ( p < 0.001). Median 'cancer worry' was lower in post-operative patients (44 vs 39, p < 0.001). Conclusion: The anglicised FACE-Q Skin Cancer module shows psychometric validity through hypothesis testing, and both classical and modern test theory.